Islamic orthodoxy-based character education: creating moderate Muslim in a modern pesantren in Indonesia - Imam Mujahid (IAIN Salatiga, 2021)
Pesantren (Islamic boarding school) has been contributing to build moderate character for Muslims in Indonesia towards globalization. However, amid peaceful Islam disseminated in the country, nowadays, radical Muslim movement challenges this character. This study aims to describe the construction of turats (traditional Muslim virtues), which has been taught in pesantren as an orthodox teachings legacy, to create young Muslim with moderate attitude through character education. It will also highlight about how and why character education with Islamic orthodoxy content is necessary to be inculcated in pesantren to produce moderate Muslim. Qualitative research was employed in this study, with a case study approach. In doing so, data collection was carried out through interviews, observation, and documents analysis techniques. The results demonstrated that the moderate character building based on the modernization of turats is derived from the renowned dogma of the ushul fiqh (traditional Islamic Jurisprudence); al muhafadhatu 'ala al-qadim as-sholih wal akhdu bi al-jadid al-ashlah (maintaining good tradition and employing the new-better one). It also revealed that within 24 hours pesantren learning activities, this jargon is disseminated to the students through the concept of Islamic guidance. In this concept, moderate character values infused to the student’s activities are rooted to the Qur'an (Muslim holy book) and Hadits (Prophet’s wisdom) as the religious foundation, the founding fathers’ vision (historical foundation), the pesantren mission (institutional foundation), and the contextual experience (empirical foundation) as well as the dynamic challenges of the globalization. The entire character education process paves a pivotal way to the moderate Muslim generation creation.